2022
DOI: 10.1002/alz.12707
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Alzheimer's disease pathology at autopsy: A systematic review

Abstract: Hypertension is an important risk factor for Alzheimer's disease (AD) and all‐cause dementia. The mechanisms underlying this association are unclear. Hypertension may be associated with AD neuropathological changes (ADNC), but reports are sparse and inconsistent. This systematic review included 15 autopsy studies (n = 5879) from observational cohorts. Studies were highly heterogeneous regarding populations, follow‐up duration, hypertension operationalization, neuropathological methods, and statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Although hypertension and AD are closely related, the mechanism responsible for the association is not clear [ 42 ]. Animal experiments indicate that hypertension activates receptors for advanced glycation end products (RAGE) in the cerebrovascular system via oxidative stress, and mediates the transcytosis of Aβ across brain endothelial cells, resulting in Aβ accumulation, cognitive impairment, and memory degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although hypertension and AD are closely related, the mechanism responsible for the association is not clear [ 42 ]. Animal experiments indicate that hypertension activates receptors for advanced glycation end products (RAGE) in the cerebrovascular system via oxidative stress, and mediates the transcytosis of Aβ across brain endothelial cells, resulting in Aβ accumulation, cognitive impairment, and memory degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is closely related to Alzheimer’s disease (AD), but the pathogenic mechanism between them is largely unclear [ 33 ]. NOS3-mediated oxidative stress is associated with amyloid-beta deposition, affecting AD development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported by the China Patient‐Centered Evaluative Assessment of Cardiac Events (PEACE) Million Persons Project, that nearly half of Chinese adults aged 35–75 years suffer from hypertension and fewer than one in twelve are in control of their blood pressure 1 . Hypertension is known to be related not only to cardiovascular events such as coronary heart disease, arrhythmia and heart failure but also to a positive association with Alzheimer's disease, 2 and a direct relationship with cancer incidence and mortality 3 . Recent studies showed that hypertension is associated with non‐alcoholic fatty liver and imbalances of intestinal flora 4,5 .…”
Section: Introductionmentioning
confidence: 99%